A surgical recovery matrix to evaluate post-surgical recovery in mice using sham and myocardial infarction models of cardiac surgery as prototypes - Eszter Pal; Brandon Shokoples; Saumya Naik; Kyle Hogue; Lorraine E. Chalifour (PLoS ONE, 2025)
Examinations of biomarkers are useful in measuring overall health. Endpoints are critical to assess the threshold where the scientific aim of the study does not prevail over the wellbeing of experimental laboratory animal. However, parameters able to assess health and recovery after an acute post-surgical intervention are needed. To fill this gap, we combined a suite of qualitative and quantitative measurements and created a surgical recovery matrix (SRM) able to monitor and score rodent health and wellbeing after surgery. We established baseline values in healthy male and female retired breeder C57BL/6N mice as a control, no surgery (NoSx) cohort. To test if SRM scoring was useful in the immediate surgical period, we monitored changes in 18 parameters after sham (SH) and myocardial infarction (MI)-inducing surgeries over 3 days of recovery. The surgical manipulations and cardiac damage involved in MI-inducing surgery render its categorization as a major surgery. In contrast, SH surgery represents a minor surgery such that the surgical manipulations are identical to that of the MI surgery but without any manipulation/damage to the heart. Six hours after surgery, males and females showed deficits in nestlet integration, eye grooming, a hunched posture and rough coat appearance whereas greater body weight losses and impaired wound healing were recorded later in the observation period. Sex-specific differences were observed such that males showed a propensity to reduced mobility and lower surface body temperature whereas females had a reduced Body Condition Score. These parameters discriminated the very low scores detected in controls from the intermediate scores after SH surgery and the highest scores in mice severely debilitated by MI surgery. Further, we identified sex-specific and time-dependent changes such that the highest scores were detected in male mice after an MI versus SH surgery. We conclude that a combination of quantitative and qualitative parameters successfully evaluated mouse recovery and health after minor and major surgery.